Gambaran Tentang Perilaku Hidup Bersih dan Sehat (PHBS) pada Siswa/Siswi di Sekolah Dasar Negeri 02 Bejen Karanganyar - Paramastri Sita Nabila; Dewi Kartika Sari (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2025)
There are still behaviors that do not align with the principles of Clean and Healthy Living Behavior (PHBS), such as littering, not washing hands with soap, and limited sanitation facilities available. According to UNICEF data (2023), the lack of handwashing habits is one of the leading causes of death from diarrhea, with 25,671 cases of diarrhea recorded in Karanganyar Regency. This study aims to assess the clean and healthy living behavior (PHBS) of students at SDN 02 Bejen Karanganyar based on eight main PHBS indicators. This research uses a descriptive quantitative method with a survey approach and stratified random sampling for data collection. The population consists of 373 students from grades I to VI, and a sample of 79 students was selected. The instrument used was a questionnaire consisting of 17 questions related to PHBS. The results show that the level of PHBS among the students of SDN 02 Bejen Karanganyar falls into the very good category, with 62% of the students in this range. The highest-scoring indicators are healthy snack consumption and waste disposal, with a percentage of 98.1%. However, the indicator for using latrines has the lowest score, which is 80.4%. The conclusion of this study is that while the clean and healthy living behavior of the students at SDN 02 Bejen Karanganyar is already quite good, improvements are still necessary, especially for the latrine usage indicator. These improvements can be achieved through continuous education on the importance of cleanliness and health, as well as improvements in supporting facilities in the school environment, such as better sanitation facilities. It is expected that with these efforts, students' awareness of PHBS will increase, and healthy living behaviors will become more integrated into their daily lives.